2011
DOI: 10.1590/s1806-83242011000600012
|View full text |Cite
|
Sign up to set email alerts
|

Gingival inflammation and platelet count in patients with leukemia: preliminary results

Abstract: Leukemia has been associated with oral manifestations. However, the available literature on this topic consists of mostly reports of cases, without data about the periodontal parameters that may be under the influence of hematologic factors. The aim of this cross-sectional study was to assess the correlation between the Gingival Index and Bleeding on Probing with the platelet count in patients with leukemia. Patients with diagnosis of any kind of leukemia, at any stage of treatment, having a minimum age of 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Moreover, the percentage of sites with bleeding had no association with platelets, but was associated with the percentage of visible plaque, contributing to the hypothesis that the gingival bleeding observed during dental examination was probably due to gingival inflammation induced by biofilm and not the systemic condition involved. These results are in agreement with other authors who did not find correlation between platelet count and gingival bleeding in leukemic patients with thrombocytopenia …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the percentage of sites with bleeding had no association with platelets, but was associated with the percentage of visible plaque, contributing to the hypothesis that the gingival bleeding observed during dental examination was probably due to gingival inflammation induced by biofilm and not the systemic condition involved. These results are in agreement with other authors who did not find correlation between platelet count and gingival bleeding in leukemic patients with thrombocytopenia …”
Section: Discussionmentioning
confidence: 99%
“…Ipak, kod bolesnika s leukemijom utvrđene su statistički značaj-no veće vrijednosti parodontoloških indeksa nevezano za dob bolesnika, što se podudara s rezultatima našeg istraživanja. Druga presječna studija, koju su proveli Angst i suradnici, obuhvaćala je 37 ispitanika s različitim vrstama leukemije, a proučavala je utjecaj trombocitopenije na gingivalno krvarenje (33). Rezultati su pokazali da je utjecaj niske razine trombocita na gingivalno krvarenje bio vrlo slab, te da statistički nije bio značajan.…”
Section: Piunclassified
“…However, in agreement with the results of our research, statistically significant higher levels of periodontal indices were found in leukemic patients compared to controls, irrespective of the patient's age. Another cross-sectional study, conducted by Angst et al, included 37 patients with different types of leukemia in which authors studied the effect of thrombocytopenia on gingival bleeding (33). The results showed that the impact of low levels of platelets on gingival bleeding was very low and was not statistically significant.…”
Section: Pimentioning
confidence: 99%
“…5 -11 Esses pacientes também podem apresentar infiltração leucêmica gengival, processos inflamatórios gengivais acentuados, sangramentos gengivais espontâneos e sangramento submucoso bucal, devido à trombocitopenia. 5,7 Durante o tratamento antineoplásico, as lesões orais (mucosite, xerostomia e infecções virais ou fúngicas) podem surgir como reações adversas, sendo as manifestações orais são mais comuns na fase de indução. 8 -12 A quimioterapia deveria destruir as células malignas, mas devido ao seu mecanismo de ação inespecífico, acaba agindo também nos tecidos normais, principalmente naqueles que possuem rápida divisão celular (mucosa bucal).…”
Section: Introductionunclassified